THE SETTLEMENT ASSESSMENT OF EFFICIENCY OF DEDUSTING SYSTEMS WITH DUST CONCENTRATORS - Natalia Mihajlovna Sergina; Elena Anatolievna Semenova (Современная наука и инновации, 2022)
One way to improve the efficiency of dust collection systems in the production of building materials is to feed streams with different dust contents to the upper and lower entrances of the vortex dust collectors. For this purpose dust concentrators can be used. A sequence of calculation of the efficiency of dust collecting systems with such devices is considered.